2015
DOI: 10.1177/0266242615618733
|View full text |Cite
|
Sign up to set email alerts
|

Bank market concentration, relationship banking, and small business liquidity

Abstract: This article examines two contrasting interpretations of how bank market concentration (Market Power Hypothesis) and banking relationships (Information Hypothesis) affect three sources of small firm liquidity (cash, lines of credit, and trade credit). Supportive of a market power interpretation, we find that in a highly concentrated banking market, small firms hold less cash, have less access to lines of credit, and are more likely to be financially constrained, use greater amounts of more expensive trade cred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 69 publications
1
10
0
Order By: Relevance
“…However, although the banking theories can have contrasting predictions (e.g. MPH vs. IBH), similar to Han et al (2017), we have shown that theories are not always mutually exclusive to each other as we find that banks with greater market power are also more likely to engage in relationship lending and reduce the information barriers between borrowers and lenders. The policy implication is that when promoting bank competition, policymakers must also pay attention to supporting SMEs' access to finance by reducing information barriers and building tailored relationship.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…However, although the banking theories can have contrasting predictions (e.g. MPH vs. IBH), similar to Han et al (2017), we have shown that theories are not always mutually exclusive to each other as we find that banks with greater market power are also more likely to engage in relationship lending and reduce the information barriers between borrowers and lenders. The policy implication is that when promoting bank competition, policymakers must also pay attention to supporting SMEs' access to finance by reducing information barriers and building tailored relationship.…”
Section: Resultssupporting
confidence: 68%
“…Di Patti and Dell'Ariccia, 2004;Cetorelli and Gambera, 2011) or two contrasting hypotheses could coexist (e.g. Han et al, 2017). Carbo-Valverde et al (2009), for example, show that market power is negatively related to credit availability only when the Lerner Index is used but concentration ratio presents opposite conclusion.…”
Section: Bank Market Power and Sme Financementioning
confidence: 99%
“…Arena and Dewally (2012) argued that firms in rural areas have a cost disadvantage in credit markets, facing higher debt yield spreads, but are more likely to rely on relationship banking, repeatedly borrowing from the same banks. Relationship banking (Han et al, 2017;Hasan et al, 2017) seems to be particularly important in less-urbanized areas, where interactions between loan officers and firm managers tend to be more frequent and fruitful, leading to the collection of better soft information. The main benefit of building close ties between firms and creditors is the availability of financing increases (Petersen and Rajan, 1994).…”
Section: Geographical Locationmentioning
confidence: 99%
“…This implies that it is possible for competition to reduce credit availability, which is consistent with the information hypothesis, arguing that increased bank competition strengthens financing obstacles and drives up lending rates. In support of market power hypothesis, Han, Zhang, and Greene (2015) showed that in a highly concentrated banking market, small firms hold less cash, have less access to lines of credit, and are more likely to be financially constrained, use greater amounts of more expensive trade credit, and face higher penalties for trade credit late payment. Their study also found support for the information hypothesis.…”
Section: Brief Literature Reviewmentioning
confidence: 99%